PROSES USULAN PEMBERIAN HAK GUNA USAHA YANG TIDAK SESUAI DENGAN PROSEDUR MENURUT PERATURAN KEPALA BADAN PERTANAHAN NASIONAL - Cahyo Fajrin Yuliansyah (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
AbstractIn order to provide legal certainty to the plantation development sector, especially in the field of land, it is necessary to have a right to land which gives authority to the right holder to control and physically entitate the land given the right. The right to land that can accommodate the field of plantation development is the Right to Use Enterprises (HGU). But on the other side of the current development of plantation land that has been clung to the Hak Guna Usaha (HGU) many claimed even occupied by the community for certain reasons that cause its own problems in order to manage plantation land.In order to grant location permit by Local Government begins with synchronization of data related institutions, so there is no overlap of licensing with the land / location of the land that will become the object of the Right to Use Enterprises.